Serial estimation of gene expression of cardiac troponin I (cTnI) and autophagy gene HMGB1 to determine postmortem interval. (May 2022) - Thakral, Sahil; Setia, Puneet; Modi, Anupama; Mishra, Richa; Meshram, Vikas; Sinha, Arvind; Purohit, Purvi
Abstract: The estimation of accurate post mortem interval (PMI) is a crucial question in forensic medicine. Several approaches have been used to determine the PMI including physical, metabolic, autolytic, entomological, physiochemical and biochemical methods over time. For estimation of PMI, RNA degradation after death is reported to be an important tool. This study aimed to analyse the pattern of gene expression by serial estimation of cardiac specific cardiac troponin I (cTnI) gene and autophagy gene HMGB1 for determining PMI at room temperature by using housekeeping gene GAPDH. Right ventricular heart tissue weighing 10 g was collected and harvested from 17 medico-legal autopsies. The tissue was homogenized in phosphate-buffered saline (PBS) on ice. Further, homogenate of cardiac tissue was analysed by quantitative Real time polymerase chain reaction (qRtPCR) for gene amplification and gene expression of cTnI, HMGB1 gene and GAPDH, at different time intervals (0, 6, 12 h) at room temperature. The result revealed ∆Ct value of cTnI gene of the cardiac muscle showing almost equal degradation at equal time interval correlated with PMI within 0–12 h at room temperature, and the ∆Ct value of HMGB1 degraded to half in every subsequent 6-hour interval at room temperature. In conclusion, the estimation of PMI by analysis of serial estimation of gene expression is a decent new tool in forensic medicine. The study shows an equal degradation of cTnI gene at equal time interval and HMGB1 degrades to half at six-hour interval. Therefore, these can be useful for estimation for PMI. Highlights: Estimation of Post-mortem interval (PMI) using cardiac specific genes and autophagy gene. Gene expression of cardiac troponin I and High-mobility group box-1 at different time interval (0, 6 and 12 h). Decrease in expression of cTnI and HMGB1 with increasing PMI. Establishing the role of gene expression by qRtPCR as an effective tool to determine PMI.